A typhoon-induced debris flow warning model integrating rainfall thresholds with geological factors - Wang, Yiming; Xu, Dengcai; Yang, Youjian; Zhou, Minglang; Chen, Wenqing; Lin, Wei (Frontiers in Earth Science, 2024)
Typhoon-induced debris flows pose a significant threat to the southeastern coastal regions of China. The existing typhoon-induced debris flow warning models, however, are largely limited in the refinement of their rainfall thresholds and in their lack of integration with geological factors. This study proposes a typhoon-induced debris flow warning model based on refined rainfall thresholds by integrating them with geological factors. Firstly, based on the characteristic rainfall of 159 debris flows in seven typhoon rainstorms between 1999 and 2019, the rainfall thresholds of debris flow under different geological conditions were obtained. Close relationships were noticed between rainfall thresholds and the number and density of debris flow disasters. The deterministic coefficient method (DCM) and sensitivity index were used to derive the weights of the geological factors, and the geological groups of the rock masses and vegetation type were the most important geological factors for debris flows. Finally, a typhoon-induced debris flow warning model was constructed, and refined rainfall thresholds were obtained. Due to different geological backgrounds, there were significant differences in the warning rainfall thresholds for debris flow disasters in different regions of the study area. The ROC indicator showed the high accuracy of this debris flow warning model. This research provides a scientific basis for the early warning and prediction of debris flows in typhoon-prone area of China.